Heterospecific sperm reduction in interspecific crosses between two closely related phytophagous ladybird beetles, Henosepilachna vigintioctomaculata and H. pustulosa (Coleoptera: Coccinellidae). Issue 1 (4th December 2015) - Kohyama, Tetsuo I.; Matsubayashi, Kei W.; Katakura, Haruo
Abstract: In interspecific crosses, a mismatch in internal physiological conditions between two species can reduce sperm viability in the interval from insemination to fertilization, leading to gametic isolation. Two closely related Japanese phytophagous ladybird beetles, H enosepilachna vigintioctomaculata and H . pustulosa, show several isolating barriers, including reduction in the number of heterospecific sperm in the female reproductive tract and low egg‐hatching rates in interspecific matings. However, the mechanisms of these two potential isolating barriers and the association between them are unknown. Here we investigated temporal changes in the number of sperm stored in the female reproductive tract and egg‐hatching rates in inter‐ and intraspecific crosses between these species. Although the number of sperm decreased after both inter‐ and intraspecific crosses, the reduction was more drastic in inter‐ than in intraspecific crosses for females of both species. Most of the sperm reduction occurred early on, during sperm transfer from the bursa copulatrix to the paired ampullae of the common oviduct (the sperm storage organs). These two species also demonstrated stably low egg‐hatching rates in interspecific crosses. Since the degree and timing of the sperm reduction did not correlate with egg‐hatching rates, the reduction in heterospecific sperm in interspecific crosses may not directly cause the low hatching rates. These two isolating barriers could be different expressions of the physiological mismatch and/or genetic incompatibility between gametes of these species. Abstract : Two closely related Japanese phytophagous ladybird beetles, Henosepilachna vigintioctomaculata and H. pustulosa, show several isolating barriers, including reduction in the number of heterospecific sperm in the female reproductive tract and low egg‐hatching rates in interspecific matings. The results of the present study revealed that most of the heterospecific sperm reduction occurred early on, during sperm transfer from the bursa copulatrix to the paired ampullae of the common oviduct (the sperm storage organs). These two species also demonstrated stably low egg‐hatching rates in interspecific crosses.